PEMENUHAN HAK KERJA PENYANDANG DISABILITAS DI KABUPATEN GRESIK: ANALISIS INSTRUMEN KEBIJAKAN DARI PERATURAN BUPATI NO. 53 TAHUN 2022 - Khuluq, Khusnul (Reflektika, 2024)
Industrial growth in Gresik Regency has created significant economic opportunities, including for people with disabilities. However, the participation rate of people with disabilities in the world of work is still relatively low. The Gresik Regency Government has issued Regent Regulation Number 53 Year 2022 on Fulfilling Equal Employment Opportunities for Persons with Disabilities to address this challenge. This study aims to analyze the effectiveness of policy instruments used in the implementation of the regent's regulation, using the theory of policy instruments by Howlett and Ramesh, which includes Voluntary Instruments, Compulsory Instruments, and Mixed Instruments. The data used includes the number of people with disabilities, the number of workers, and company participation in providing employment opportunities for people with disabilities. The results show that this policy has the potential to increase social inclusion and employment opportunities for people with disabilities through collaboration between the government, private sector, and community. However, challenges such as discrimination, lack of accessibility, and lack of inclusive training still require serious attention. This study provides recommendations for the optimisation of policy instruments to support the successful implementation of the Bupati Regulation No. 53 Year 2022.